Efecto de la tecnología de recubrimiento con carburo de tungsteno sobre costos de mantenimiento en desfibramiento de caña azucarera, 2017. - Torres Rivera, Christian Michell (2019)
ABSTRACT The main objective of this study was to help decision-making when choosing the appropriate technology to carry out the maintenance of sugarcane shredding equipment and its parts of a local agroindustrial company. In the same way it was tried to demonstrate with the present work, the application realized in the chosen sugar company, specifically the sugarcane shredding equipment, was influenced in a significant way by the application of the protective coating, Hardfacing, with tungsten carbide in particles in its components of wear and over their maintenance costs. To achieve this, a coating application test with tungsten carbide in particles was implemented on a complete set of shredders, replacement parts, in order to perform the method of comparison with the parts, which use the traditional protective coating technology with chrome carbides. The results obtained in the analysis of the information, has shown that the cost of maintenance; represented by the operation cost, replacement of parts and lost time were lower when using the technology of protective coating with tungsten carbide in particles being the main component of replacement parts cost. The main conclusion of this report was in favor of the use of the protective coating technology with particulate tungsten carbide on the replacement parts of the sugarcane shredding equipment due to its economic savings in the cost of maintenance.